Establishment of Hevea brasiliensis lines overexpressing genes involved in ethylene signalling pathway - Retno LESTARI; Maryannick RIO; Florence MARTIN; Julie LECLERCQ; Florence DESSAILLY; . SUHARSONO; Pascal MONTORO (Menara Perkebunan, 2016)
The gaseous plant hormone ethylene has a wide variety of applications in agriculture and horticulture. Ethylene Response Factors (ERF) are the last transcription factors of the ethylene signalling pathway and control a large number of ethylene-responsive genes. Two Hevea brasiliensis ERF, HbERF-IXc4 and HbERF-IXc5, are orthologs to ERF1 a key regulator at the crosstalk of ethylene and jasmonate signalling pathways. These genes were suggested to play an important role in regulating latex cell metabolism in response to tapping and ethephon stimulation. In this study, transgenic lines overexpressing HbERF-IXc4 and HbERF-IXc5 under control of 35S CaMV and HEV2.1 promoter have been conducted. Transgenic Hevea lines were obtained by Agrobacterium tumefaciens-mediated genetic transformation. The somatic embryogenesis process was affected by these modifications. Agrobacterium tumefaciens genetic transformation procedure has been developed from friable callus line for clone PB260. Hevea callus was sub-cultured as small aggregates on paromomycin selection medium. Transgenic callus lines were established from sub-aggregates showing full GFP activity. Ten transgenic lines were confirmed as transgenic by Southern blot hybridization. This result showed successfully establishment of H. brasiliensis transgenic lines. Further plant regeneration and characterization were necessary to understand the function HbERF-IXc4 and HbERF-IXc5 in latex.